Tips and Tricks to Master English Vocabulary at SMPN 3 Lintong Nihuta - Siahaan, Rekolina (UKInstitute, 2025)
Vocabulary is a fundamental component in learning English, especially at the junior high school level. A strong vocabulary foundation supports students' skills in understanding, speaking, writing, and listening to English effectively. However, in reality, many junior high school students struggle to expand and retain the vocabulary they have learned. This community service activity aims to help junior high school students master English vocabulary through an interactive and enjoyable approach. The methods used in this activity include material delivery, educational games, the use of visual media, and direct practice within sentence and conversation contexts. The results of this activity show that students are more enthusiastic about learning, understand strategies that can be applied independently, and demonstrate improvement in actively using vocabulary. It is hoped that this activity can serve as a sustainable effort to enhance English competence among junior high school students.